Epidemiology of fluorosis and dental caries according to different types of water supplies - Franzolin, Solange de Oliveira Braga; Gonçalves, Aguinaldo; Padovani, Carlos Roberto [UNESP]; Francischone, Leda Aparecida; Marta, Sara Nader (Associação Brasileira de Saúde Coletiva (ABRASCO), 2010)
O objetivo do presente artigo é investigar a relação fluorose/cáries em escolas, de acordo com o nível de fluoreto no abastecimento público de água. A amostra consistiu em 360 alunos de doze anos de idade, de ambos os sexos, que frequentam as escolas próximas da região em que nasceram. As escolas foram classificadas em três grupos de acordo com a presença de fluoreto no abastecimento de água: 1) fluoretação na Estação de Tratamento de Água (ETA); 2) fluoretação direta em poços; e 3) áreas não fluoretadas (ANF). Os testes deχe de Goodman (significância = 5%) foram utilizados para avaliar a associação entre a origem da água e o grau de fluorose. Os resultados mais predominantes foram presença de cáries em toda a amostra (P<0,05); ausência de fluorose em ambos gêneros, para indivíduos brancos e aqueles vivendo em áreas abastecidas com água fluoretada diretamente de poços e não fluoretadas (P<0,05). Não houve diferença no grau de severidade da fluorose entre as fontes de abastecimento de água (P>0,05). As cáries ainda são uma importante questão nessa população, apesar do estabelecimento de medida preventiva. A observação da fluorose em alunos vivendo em áreas não fluoretadas confirma a presença de outras fontes de fluorose.

The aim of this article is to investigate the relationship between fluorosis/dental caries in schools, according to the level of fluoride in public water supply. The sample comprised of twelve-year-old daytime students (360) of both genders, attending schools close to the region where they were born. The schools were classified into three groups according to the presence of fluoride in the water supply: 1) fluoridation in the Water Treatment Station-WTS; 2) Direct Fluoridation in Wells-DFW; and 3) Non Fluoridated Areas-NFA. The χ2 and Goodman tests (significance=5%) were used to evaluate the association between the origin of water and degree of fluorosis; percentage of distribution and descriptive measures were used for investigation of the degree of fluorosis. The following outcomes were predominant: presence of dental caries in the entire sample (P<0.05); absence of fluorosis in both genders, for white individuals and subjects living in areas supplied by both DFW and NFA (P<0.05). There was no difference in the severity of fluorosis between the sources of water supply (P>0.05). Dental caries is still an important problem in this population, despite the establishment of preventive measured. The observation of fluorosis in students living in non-fluoridated areas confirms the presence of other sources of fluoride.
Epidemiologia da fluorose e cáries dentárias de acordo com diferentes tipos de abastecimento de água
Keywords: Fluorose; Cáries dentárias; Fluo-reto; Abastecimento de água; Tratamento de água; Fluorosis; Dental caries; Fluoride; Water supply; Water treatment